1990
DOI: 10.1111/j.1540-4781.1990.tb05335.x
|View full text |Cite
|
Sign up to set email alerts
|

The Naive Lexical Hypothesis: Evidence from Computer‐Assisted Language Learning

Abstract: COMPUTER-ASSISTED LANGUAGE LEARNING(CALL) environments provide tools such as word-processing and database searching which encourage creative interaction by students with a rich environment for foreign language learning supported by databases of reference materials.! The new technology also encourages the direct involvement of instructors in the learning process, by offering the possibility of recording student responses and response paths in real time. This previously inaccessible "window" into the students' s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 3 publications
1
24
0
Order By: Relevance
“…Similarly, while using ESL/EFL reading courseware with multiple types of annotations, Laufer and Hill (2000) found that students predominantly consulted information on word meanings. In a pair of classic studies, working with Système-D (a French writing assistant program for students that contained a bilingual dictionary, a functional reference grammar, and a verb conjugator), Bland, Noblitt, Gay, and Armington (1990) and Noblitt and Bland (1991) remarked that students used the dictionary for English-to-French translations fully 80% of the time. Hulstijn (1993) found great variability in students' consultations of word definitions in a CALL-based reading program and observed that some students skipped entire paragraphs in the reading passage even though they knew they were going to be tested on the content of the passage (also see Hwu, 2004).…”
Section: Software Evaluationmentioning
confidence: 98%
“…Similarly, while using ESL/EFL reading courseware with multiple types of annotations, Laufer and Hill (2000) found that students predominantly consulted information on word meanings. In a pair of classic studies, working with Système-D (a French writing assistant program for students that contained a bilingual dictionary, a functional reference grammar, and a verb conjugator), Bland, Noblitt, Gay, and Armington (1990) and Noblitt and Bland (1991) remarked that students used the dictionary for English-to-French translations fully 80% of the time. Hulstijn (1993) found great variability in students' consultations of word definitions in a CALL-based reading program and observed that some students skipped entire paragraphs in the reading passage even though they knew they were going to be tested on the content of the passage (also see Hwu, 2004).…”
Section: Software Evaluationmentioning
confidence: 98%
“…That is why the difficulty in mastering these language components, grammar and vocabulary will of course contribute to the inability to write a text well. As cited by Kern (2000: 171) from the studies conducted by Bland, Noblitt, Armington and Gay (1990), the early learners of a new language were dominated by the difficulty in vocabulary; while the advanced learners as students in universities are dominated by the genres and rhetorical organization problems. Consequently, the text they write often does not show its unity or incoherent for they don't know much how to link This problem leads the writer to investigate whether or not the students' abstracts of their final project reports are coherent and cohesive.…”
mentioning
confidence: 99%
“…The data gathered from Research Question One corroborate earlier findings by Hsu, Chapelle, and Thompson (1993) and Bland, et al (1990), which show that learners do not access all the available information when working in an interactive CALL environment. As mentioned earlier, even though the repeat button was the only option for modification of input that was explicitly introduced to the students, 15 of the 91 still did not use it.…”
Section: Insights For Researcherssupporting
confidence: 80%
“…The following were considered options for the user: the ABC button, the repeat button, the glossary, the microphone button, the headphone button, and a speech recognition (SR) task attempt. Hypothesis 1 (HI) was constructed based upon past research by Bland, et al (1990) and Hsu, Chapelle, and Thompson (1993): this research was expected to reveal that students would use some options more than other options and that this choice would vary from student to student.…”
Section: Discussionmentioning
confidence: 99%